Regulación de energías renovables en Colombia (2017)
In this document aims to give an answer to the importance of regulation in the matter on non-conventional energies or renewable energies, regulation that in the interior of our territorial order does not exist. A regulation in Colombia will benefit the environment that would prevent scenarios of non-renewable extraction and exploitation resources from continuing, and avoiding a negative impact on ecosystem equilibrium. It will also benefit the economic sector to the extent that delimits and stablish clear rules for individuals who want to be part of the economic sector here, lower than other competitors in the market.